PENGARUH KUALITAS PRODUK UKM DAN MEDIA SOSIAL TERHADAP MINAT BELI ULANG DENGAN KEPUASAAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Novia Indah Lestari; Heni Iswati (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
Small and medium enterprises (SMEs) in Bandung city are growing rapidly. The intense competition between SME entrepreneurs encourages SME entrepreneurs to continue to improve the quality of their products. In addition, the media for offering and selling SME products, namely social media, is increasingly being used because it is more effective and efficient in disseminating information. The purpose of this study was to determine the effect of SME product quality and social media on repurchase interest with customer satisfaction as an intervening variable in the city of Bandung. The method used in this research is descriptive verification with a quantitative approach to consumers who have purchased SME products through social media and obtained data of 318 respondents via google form who have met the requirements for processing. Descriptively, it was found that all variables were categorized as